Sorensenite, a new Sodium-Beryllium-Tin-Silicate from the Ilímaussaq Intrusion, South Greenland. - Semenov, E. I.; Gerassimovsky, V. I.; Maksimova, N. V.; Andersen, S.; Petersen, O. V, (Meddelelser om Grønland, 1965)
The new mineral sorensenite (Na4SnBe2Si6O16(OH)4 ) occurs in groups of prisms attaining diameters of several centimetres. The mineral is transparent or semitransparent, colourless, brown or pink. The crystals are monoclinic, a0 = 18.58, b0 = 7.45 and c0 = 12.05, β = 98°09’. Space group - 12/a, - I a. There are two distinct cleavages. The specific gravity is 2.9, the hardness 5-5.5. The mineral sometimes forms flat pseudohexagonal triplets with the normal to ( 011) in (100) as twin axes. The mineral is biaxial negative, 2 Vα= small to 75°, nα = 1.576-1.579, nβ = 1.581- 1.585 and nγ = 1.584-1.586. The chemical analysis (by M. E. KAZAKOVA): SiO2 49.73, SnO2 20.07, Nb2O5 0.75, Fe2O3 0.04, BeO 8.02, Na2O 15.95, K2O 0.34, H2O 5.24; total 100.14 corresponds to the formula: Na4SnBe2Si6O16(OH)4. The mineral occurs in analcime-rich bodies in nepheline-sodalite-syenites of the Ilímaussaq massif, South Greenland. It is abundant in a few localities. Sorensenite is named after professor HENNING SØRENSEN, Copenhagen, who directs the investigations in the Ilímaussaq region.